The Effects Of Prehabilitation Exercise Using Resistance Bands On Functional Performance In Total Knee Replacement - Rahmatika Rahmatika; Robin Novriansyah; Lanny Indriastuti (Indonesian Hip and Knee Society (IHKS), 2020)
Background:Despite the high succesful rate of Total Knee Replacement (TKR), there are still patients with permanent dysfunction and a longer period of rehabilitation that interfere with functional performance. Strengthening exercise before TKR namely prehabilitation exercise using resistance bands is expected to optimize patient’s condition before surgery that will increase functional performance after TKR and accelerate rehabilitation programs.Methods:16 eligible patients were allocated into the treatment group (n=8) and the control group (n=8). The treatment group received 4 weeks of prehabilitation exercise with a frequency of 2 times and one time as a home program. The control group only received conventional therapy. The TUG and WOMAC scores were measured 3 times; at baseline, after 4 weeks of prehabilitation exercise and at 8 weeks of rehabilitation after TKR.Results:Before intervention, there were no significant differences between groups for the TUG score (p=0.674) and WOMAC (p=0.928). After 4 weeks of intervention, there was significant difference in the TUG score (p=0.003) and WOMAC (p=0.002), whereas at 8 weeks after rehabilitation programs there was a significant difference in the TUG score (p=0.009) while for the WOMAC score there was no significant difference (p=0.125).Conclusion:Prehabilitation exercise using resistance band improved functional performances in patients undergone TKR.